(untitled) (Applied Biological Research, 2023)
An ectoparasitic survey on fish Wallago attu (n = 95) of river Penna, YSR district, Andhra Pradesh (India) was executed from August, 2017 to February, 2018. A total of 3202 parasites belonging three ectoparasitic groups viz., three monogeneans - Thaparocleidus indicus, thaparocleidus wallagonius, Mizelleus indicus, one copepod - Ergasilus malnadensis, and one isopod - Alitropus typus were detected from the gills of the examined hosts. Their spatial distributions on the host gills were reported. Only E. malnadensis, T. wallagonius and T. indicus showed aggregate distribution while the remaining two species, M. indicus and A. typus showed random distribution. Only, A. typus, T. wallagonius and T. indicus showed positive and statistically significant correlation with the condition factor. Location wise ectoparasite analysis revealed the higher infestation rates in site-II Somasila backwaters, Vontimitta compared to site-I Chennur. Spatial distribution studies revealed that there is no significant preference for the sides of the host fish. Both the sides of gill arch wereequally infected. However, they showed preference within the gill arches. Monogeneans preferred gill arches II, III and IV, whereas copepods and isopods preferred gill arches I and II. There was meagre effect of host size and host sex on the ectoparasitic infection. These types of spatial distribution studies give an accurate location of the parasites to apply the eradication measures and eradicate them efficiently in fish aquaculture.